Selected legal issues of livestock farming in the light of new legal regulations - Lipińska, Izabela; Hasińska, Izabela (Przegląd Prawa Rolnego, 2020)
The purpose of the considerations was to answer the question whether the legal standards governing livestock farming adopted at the EU level serve the purpose of proper organisation of animal husbandry and whether the Polish legislator has ensured appropriate solutions enabling proper implementation of European Union law. The conclusions of the considerations are that European Zootechnical Legislation has been simplified, allowing for a smooth and effective conduct of livestock farming. The new Act on the organisation of breeding and reproduction of farm animals enables full and correct implementation of the EU regulation in Poland. At the same time, the requirement arising from the Act to conduct assessments of the utility and genetic value of animals and to maintain herd books and records guarantee the durability of livestock farming.